Sociology of Drug Consumption (Drug Control Headquarters, Research and Education Office, 2004)
In this article which is a review of sociological ideas and studies of drug abusers in social situation, drug addiction steps (particularly alcohol, heroin and cocaine consumption) are revised and some explanations are made. Also, the role of some sociological ideas in drug addiction is considered in which Anomie Theory reads: "because of such duality, the individuals who are not satisfied with their role are in hurt." According to this theory, drug users choose seclusion and neglecting usual social aims as well as competitive situations. Association of Differentiation Theory claims that drug use behavior is a learned behavior and the first learning occurs in a friendly small group (i.e. youngsters). Social Control theory believes that one can predict normal and abnormal behaviors through the rate of individuals' social commitments. Internal and external controls also determine commitment rate. Micro-cultural theory considers drug use as a compatibility with abnormal micro-culture rules. Symbolic Mutual Action Believes that the etiquettes which society attribute to individuals/behaviors determine their acquired social reactions rather than any inherited acquisition.